The Leadership Model 4.0 for the Directors of Private General Education Schools: Case Study in Bangkok Metropolis - เทศน้อย, เพลินพักตร์; สุวรรณสาร, ชัยณรงค์; ภัทราวิวัฒน์, กาญจนา (JOURNAL OF SOUTHERN TECHNOLOGY, 2019)
The purposes of this research were (1) to develop the Leadership Model 4.0 for the Directors of Private General Education Schools: Case study in Bangkok Metropolis, (2) to verify the validity of the model, and (3) to seek the outstanding components and the components needed to be developed of the Leadership Model 4.0 for the Directors of Private General Education Schools in Bangkok. This research was carried on two types of research methodologies, qualitative and quantitative mixed methods. At the beginning, the qualitative method was practiced to study and identify the Leadership Model 4.0 for the Directors of Private General Education Schools by studying the transformational leadership theories, national development policy “Thailand 4.0 Model”, Thai Education 4.0, and other related literature. Then, the researcher interviewed 5 professionals in educational field to collect data, using in-depth interview method. After that, focus group discussion was conducted to draft the Leadership Model 4.0 for the General of Private General Education Schools. Once qualitative data was completely collected, it was analyzed to create the questionnaire and the researcher started qualitative method afterwards. The questionnaires were sent to the sample group of 220 directors from the total of 709 private general schools in Bangkok by using a Simple Random Sampling. Confirmatory Factor Analysis was run by Analysis of Moment Structure: AMOS program to test the validation of the research hypothesis model. The main findings were 1) the Leadership Model 4.0 for the Directors of Private General Education Schools: Case Study in Bangkok Metropolis was consisted of 3 aspects, namely, the transformational leadership, the characteristics of Leadership 4.0 and the role and duty of the director. 2) The validation of the leadership measurement model 4.0 for the Directors of Private General Education Schools in Bangkok was in accordance with the empirical data. The value of CMIN/DF = 2.987, GFI = 0.976, NFI = 0.988, RFI = 0.870, IFI = 0.992, TLI = 0.910, CFI = 0.992, RMSR = 0.006, and RMSEA = 0.10. The Standardize Regression Weight of each latent variable was statistically significant to the model. 3) The outstanding variables were shown in all three aspects, i.e., the transformational leadership, the characteristics of Leadership 4.0 and the role and duty of the director. On the contrary, there were some variables shown the need to be developed such as, instructional leadership from role and duty of the director aspect as well as visionary and clear in vision from transformational leadership aspect.